Individual and environmental correlates of objectively measured physical activity and sedentary time in adults from Curitiba, Brazil - Gonçalves, Priscila Bezerra (Int J Public Health, 2017)
OBJECTIVES: This study assessed the association of individual and neighborhood environment characteristics and objectively measured physical activity (PA) and sedentary time (ST) in adults from Curitiba, Brazil. METHODS: A population-based cross-sectional study was conducted through face-to-face household interviews in 2010. The analytic sample included 305 adults aged 20–65 years recruited from 32 census tracts selected according to neighborhood walkability and socioeconomic status. Individual and environmental PA correlates were evaluated through standardized and valid self-reported measures, including the Neighborhood Environment Walkability Scale. Minutes per week of PA and ST were assessed through accelerometry. Multi-level regression models were used in the analyses. RESULTS: After adjusting for confounders the strongest individual and environmental correlates associated with ST was residential density (B = 0.14; p = 0.008), light-intensity PA was being a father/mother (B = 35.71; p = 0.025) and moderate-to-vigorous PA was sex (B = 0.91; p < 0.001) and number of cars (one car, B = −1.05; two cars, B = −1.14; p < 0.001). CONCLUSIONS: The associations found with individual and environmental correlates varied accordingly across all outcomes. Future changes in policies and infrastructure should consider the social context of the community and improvements to promote a safer environment in the neighborhood.